Raziskave cevi uparjalnika - Vojvodič-Tuma, Jelena (Kovine zlitine tehnologije, 1999)
The addy current testing of the steam generator of nuclear power plant Krško are discussed. After 121.000 hours of operation the surface of transport of heat from the primary to secondary part of the plant is diminished consequently by 17,4% and it is near the limit of the licenced operation at full power. The last investigations in 1998 confirmed that the operation time of the steam generators is running out.
Keywords: jedrski reaktorji; uparjalniki; cevi; preiskave